Structural and Functional Analysis of the Pore-Forming Toxin NetB from Clostridium perfringens - Xu-Xia Yan (American Society for Microbiology, 2013)
ABSTRACT Clostridium perfringens is an anaerobic bacterium that causes numerous important human and animal diseases, primarily as a result of its ability to produce many different protein toxins. In chickens, C. perfringens causes necrotic enteritis, a disease of economic importance to the worldwide poultry industry. The secreted pore-forming toxin NetB is a key virulence factor in the pathogenesis of avian necrotic enteritis and is similar to alpha-hemolysin, a β-barrel pore-forming toxin from Staphylococcus aureus. To address the molecular mechanisms underlying NetB-mediated tissue damage, we determined the crystal structure of the monomeric form of NetB to 1.8 Å. Structural comparisons with other members of the alpha-hemolysin family revealed significant differences in the conformation of the membrane binding domain. These data suggested that NetB may recognize different membrane receptors or use a different mechanism for membrane-protein interactions. Consistent with this idea, electrophysiological experiments with planar lipid bilayers revealed that NetB formed pores with much larger single-channel conductance than alpha-hemolysin. Channel conductance varied with phospholipid net charge. Furthermore, NetB differed in its ion selectivity, preferring cations over anions. Using hemolysis as a screen, we carried out a random-mutagenesis study that identified several residues that are critical for NetB-induced cell lysis. Mapping of these residues onto the crystal structure revealed that they were clustered in regions predicted to be required for oligomerization or membrane binding. Together these data provide an insight into the mechanism of NetB-mediated pore formation and will contribute to our understanding of the mode of action of this important toxin. IMPORTANCE Necrotic enteritis is an economically important disease of the worldwide poultry industry and is mediated by Clostridium perfringens strains that produce NetB, a β-pore-forming toxin. We carried out structural and functional studies of NetB to provide a mechanistic insight into its mode of action and to assist in the development of a necrotic enteritis vaccine. We determined the structure of the monomeric form of NetB to 1.8 Å, used both site-directed and random mutagenesis to identify key residues that are required for its biological activity, and analyzed pore formation by NetB and its substitution-containing derivatives in planar lipid bilayers.